Growth responses of entire and immunocastrated male pigs to dietary protein with and without ractopamine hydrochloride. (20th February 2017) - Needham, T.; Hoffman, L. C.; Gous, R. M.
Abstract : The interaction between dietary balanced protein, ractopamine (RAC) and Improvac (IMP) on the growth response of 120 individually penned male PIC © pigs was evaluated. The pigs entered the trial at 16 weeks of age and were assigned to 12 treatments using a 2×2×3 factorial design. Three balanced protein diets, formulated with standard illeal digestible lysine levels of 7.50 (low), 9.79 (medium) and 12.07 g/kg (high), were fed from 20 weeks. Improvac was administered at 16 and 20 weeks, the booster being given 4 weeks before slaughter. Ractopamine was supplemented at 10 mg/kg to the applicable treatments from 20 weeks. Live weight, backfat depth and food intake were measured on a weekly basis. Primary vaccination had no influence on the parameters measured. Immunocastration, RAC and higher protein diet treatments increased weight gain, but food intake was increased only with the use of IMP. Although weight gain increased in IMP-treated males, the increased feed intake resulted in their feed conversion efficiencies (FCE) being inferior to the intact controls. Feeding RAC only benefitted FCE when a high or medium protein diet was fed. Immunocastrates deposited more backfat after the booster vaccination than did entire males. Thus the cost of using RAC, IMP and of increasing dietary protein content needs to be weighed up against the additional revenue generated through the use of these interventions.